NHC/Phosphite Nickel(II) Precatalysts for the C-N Cross-Coupling of (Hetero)Aryl Chlorides under Mild Conditions - Darandale, Nutan R.; John, Morgan E.; Moggach, Stephen A.; Sawant, Dinesh N.; Koutsantonis, George A.; Dorta, Reto; Stewart, Scott G. (ORGANIC LETTERS, 2025)
We report the synthesis of three nickel complexes based on Ni(NHC)[P(OR)3](Ar)Cl and their application in C(sp 2)-N cross-coupling reactions. Reactions involving secondary amines proceeded at room temperature, while anilines and primary alkyl amines coupled under mild heating. The reported complexes are air-stable as solids, operate at low catalytic loading, and do not require an exogenous ligand. Mechanistic studies suggest both free and Ni-bound phosphite are present during the reaction and that an isolated [Ni(NHC)(amine)(Ar)Cl] complex could be an on-cycle, catalytically active species.